Macro and Micro Level Analysis of Indonesian Business E-mail Written By Minangkabau and Javanese Speakers: Array - Geubrina, Misla (Universitas Harapan Medan, 2022)
The comparison of the approach totally different individuals with different language backgrounds adopt the Indonesian in their e-mails will yield useful findings and may illuminate the extent to that the e-mail messages or influenced by the interlingual and intercultural transfer. This analysis aims to explain the interrelatedness among genre analysis of Indonesian business e-mails written by Minangkabau and Javanese Speakers. The method used descriptive qualitative. The information was obtained from ten business e-mails written by Minangkabau (five business e-mails) and Javanese Speaker (five business e-mails) and analyzed those supported 2 major stages, namely: macro-level and micro-level analysis consistent with Santos (2002). The results obtained from this analysis were Minangkabau speaker had additional complete structure than Javanese speaker. Because, in business e-mails written by Minangkabau had additional complete in move than Javanese speakers. And in lexico-grammatical options, the Javanese prefer to use proper noun, and therefore the Minangkabau prefer to use function word “you”.